(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Differentiated thyroid carcinoma (DTC) is the most common endocrine malignancy, which is successfully treated with total thyroidectomy or near-total thyroidectomy followed by radioactive iodine ablation/radioactive iodine therapy of remnant tissue. Incidental parathyroidectomy is a common complication during total thyroidectomy or near-total thyroidectomy, leading to hypoparathyroidism, requiring calcium and vitamin D supplementation to maintain calcium homeostasis. These patients are also treated with levothyroxine (LT4) to suppress thyroid-stimulating hormone (TSH) and prevent recurrence or metastasis, which is known to impact bone mineral density (BMD) due to increased bone turnover. As osteoporosis is a significant public health concern, this study evaluates the effects of long-term TSH suppression and calcium-D3 therapy on BMD in post-thyroidectomy DTC patients. Objective: The primary aim of this study was to assess the impact of prolonged TSH suppressive therapy and high-dose calcium-D3 supplementation on BMD in DTC patients with incidental parathyroidectomy during thyroidectomy followed by radioactive iodine ablation. Patients and Methods: This observational cross-sectional study was conducted at the National Institute of Nuclear Medicine & Allied Sciences (NINMAS), BSMMU campus, Dhaka, over a period of 18 months from February 2023 to July 2024. A total of 103 post-thyroidectomy DTC patients aged between 20 and 45 years, all of whom had incidental parathyroidectomy, were included. BMD was measured using dual-energy X-ray absorptiometry (DEXA) at the lumbar spine (LS) (L1-L4 vertebrae) and both femoral necks (FN). Independent variables, including the duration of therapy, daily doses of LT4, and calcium-D3, were analyzed in relation to BMD Z-scores and T-scores. Result: Study included 103 participants (M= 12, F= 91) with a mean age of 34.5 ± 6.3 years. The average duration of LT4 and calcium-D3 therapy was 7.23 ± 2.99 years. According to BMD Z-scores, four patients had low bone mass at the lumbar spine and one at the left femoral neck. Osteoporosis, as defined by T-scores, was found in one patient at the lumbar spine, while osteopenia was observed in 22 patients at the lumbar spine and five at the femoral neck. No significant association was found between LT4/calcium-D3 therapy duration and BMD scores at the lumbar spine or femoral neck. Similarly, no significant correlation was observed between therapeutic doses, age, body mass index and BMD Z-scores or T-scores (p > 0.05). Conclusion: Long-term TSH suppression combined with calcium-D3 supplementation in premenopausal females and young male DTC patients does not significantly affect bone mineral density. Bangladesh J. Nuclear Med. 27(2): 222-228, 2024